Effect of Electroacupuncture on Gut Microbiota in Participants With Knee Osteoarthritis - Wang, Tian-Qi; Li, Ling-Ru; Tan, Chun-Xia; Yang, Jing-Wen; Shi, Guang-Xia; Wang, Li-Qiong; Hu, Hui; Liu, Zhi-Shun; Wang, Jun; Wang, Tong; Yuan, Yong; Jia, Wen-Rui; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
A close relationship between knee osteoarthritis and gut microbiota disorders has recently been described. Herein, we aim to investigate the effect of electroacupuncture on gut microbiota in participants with knee osteoarthritis. We conducted a study of 60 participants with KOA and 30 matched healthy controls. Sixty participants were allocated to either electroacupuncture (EA) group (n=30) or sham acupuncture (SA) group (n=30). EA group was treated by five obligatory acupoints and three adjunct acupoints. Eight non-acupoints that were separated from conventional acupoints or meridians were used for the SA group. Both groups received 24 sessions within eight weeks. Faecal microbial analyses were carried out after collecting stools at T0 and T8 weeks, and microbiomes were analyzed by 16S ribosomal RNA gene sequencing. A significant structure difference of gut microbiota between KOA participants and healthy controls (HCs). Difference was observed in both α and β diversity. Two genera separated KOA from HCs, out of which Streptococcus (q=0.01556) was increased in KOA participants, while Bacteroides (q=0.04505) was decreased in Kruskal-Wallis H test. After treatment, the amount of Streptococcus (q=0.003) in EA group had statistically decreased while Ruminococcus (q=0.030), Faecalibacterium (q=0.029) and Agathobacter (q=0.006) were increased in wilcox-test. EA group decreased more in WOMAC total score (all P<0.05) and NRS score (P=0.002) than those in SA group. Adverse events were low and similarly distributed between groups. Ruminococcus and WOMAC total score was negatively correlated (P=0.044). Streptococcus was positively correlated with WOMAC total score (P=0.044) and Escherichia-Shigella was positively correlated with NRS score (P=0.024).